Engineered Cementitious Composites (ECC) Bendable Concrete for Sustainable and Resilient Infrastructure - Li, Victor C. (Springer Berlin Heidelberg : Imprint: Springer, 2019)
This is the first book on Engineered Cementitious Composites (ECC), an advanced concrete material attracting world-wide attention in both the academic community and in industry. The book presents a comprehensive coverage of the material design methodology, processing methodology, mechanical and durability properties, smart functions, and application case studies. It combines effective use of illustrations, graphical data, and tables. It de-emphasizes mathematics in favor of physical understanding. The book serves as an introduction to the subject matter, or as a reference to those conducting research in ECC. It will also be valuable to engineers who need to quickly search for relevant information in a single comprehensive text.